2017
DOI: 10.2196/jmir.6994
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Preferences for an Asthma Self-Management App Highlight Psychological Needs: A Participatory Study

Abstract: BackgroundAlthough the prevalence of mental illness among young people with asthma is known to be twice the rate of the wider population, none of the asthma apps reported have acknowledged or attempted to include psychological support features. This is perhaps because user involvement in the development of asthma apps has been scarce. User involvement, facilitated by participatory design methods, can begin to address these issues while contributing insights to our understanding of the psychological experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 40 publications
2
97
0
Order By: Relevance
“…Other studies also showed similar results. 16,46 In a study by Geryk et al (2016), the parents of children with asthma reported "recording data, physician communication, and sharing data via e-mail" and physicians reported "reminder for physician appointment" as the most important functionalities of the applications. 47 But because of the difference in targeting groups, asynchronous communication via e-mail and lack of sufficient time for physicians to connect to the internet, 48,49 this functionality was different in our study than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed similar results. 16,46 In a study by Geryk et al (2016), the parents of children with asthma reported "recording data, physician communication, and sharing data via e-mail" and physicians reported "reminder for physician appointment" as the most important functionalities of the applications. 47 But because of the difference in targeting groups, asynchronous communication via e-mail and lack of sufficient time for physicians to connect to the internet, 48,49 this functionality was different in our study than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The first article stated that theoretical thematic analysis resulted in a set of personal needs, feature ideas, and app of the relevant features by young people for an asthma support app. The data mentioned that psychological factors such as anxiety, and impediments to autonomy, competence, and relatedness (as consistent with self-determination theory [SDT]), were considered major influences on quality of life by young people with asthma (Peters et al, 2017).…”
Section: The Need To Add App Contentmentioning
confidence: 86%
“…However, two factors should be considered when developing software applications to support first year university students. First, end-user involvement in the design process is important to the success of the software (Cho et al, 2014;Dunton et al, 2014); Second, there is only a weak connection between theories and how they should be implemented in terms of software features (Peters et al, 2017). Therefore, a user-centered design (UCD) approach was adopted in this study.…”
Section: School Of Electrical and Information Engineering The Univermentioning
confidence: 99%